Almási, Gábor and Lav Šubarić, eds. 2015. Latin at the Crossroads of Identity. Leiden: Brill. 326 pp. - Siarl Ferdinand (Hungarian Cultural Studies, 2016)
Almási, Gábor and Lav Šubarić, eds. 2015. Latin at the Crossroads of Identity. Leiden: Brill. 326 pp.